Posterior reversible encephalopathy syndrome after CD19 chimeric antigen receptor therapy for B-acute lymphoblastic leukemia: case report - Agarwal, Rohan Dipesh; Kunwor, Ranju; Sudanagunta, Kavya (Frontiers in Oncology, 2025)
Posterior reversible encephalopathy syndrome (PRES) is a neurologic condition characterized by distinctive radiologic findings and altered mental status, often associated with chemotherapy or systemic endothelial dysfunction. To date, there have been no documented cases of PRES occurring after chimeric antigen receptor T cell therapy (CAR-T) for B-cell acute lymphoblastic leukemia (B-ALL). We describe the case of a 30-year-old female patient with relapsed B-ALL who received brexucabtagene autoleucel and subsequently developed a progressively worsening cytokine release syndrome and immune effector cell-associated neurotoxicity syndrome. On day 15 post-infusion, she developed acute encephalopathy and hypertension. The brain MRI revealed new, symmetric bilateral cortical and subcortical T2/fluid-attenuated inversion recovery hyperintensities consistent with a diagnosis of PRES. Treatment with multiple courses of anti-seizure medications, anti-cytokine therapy, and high-dose pulse corticosteroids led to complete clinical recovery and resolution of the imaging abnormalities. To our knowledge, this represents the first reported case of PRES following CD19-directed CAR-T for B-ALL. This case highlights the potential for PRES as a complication of CAR-T mediated by cytokine-induced cerebrovascular endothelial injury. It also raises the possibility that a prior history of vasculitis, such as lymphomatoid granulomatosis, may predispose patients to an elevated risk of developing CAR-T-associated PRES.